Rock art studies : news of the world. - Bahn, Paul G.,; Franklin, Natalie R.,; Strecker, Matthias, (Archaeopress Archaeology, 2021)
Like previous series entries, this volume covers rock art research and management all over the world over a 5-year period, in this case 2015-19. Contributions once again show the wide variety of approaches that have been taken in different parts of the world and reflect the expansion and diversification of perspectives and research questions.